A Comparison between Er,Cr:YSGG 2780 nm Laser and Carbide Fissure Bur in Root-End resection - Almiran, Doaa A.; Alkurtas, Salah A. (Iraqi Journal of Laser, 2020)
Aim: The Aim of the study is to compare between Er,Cr:YSGG 2780 nm laser and carbide fissure bur in root-end resection regarding the morphological variations, temperature changes and the duration of resection process. Settings and Design: 5 W, 25 Hz, 50% water, 80% air,25.47 J/cm2 . Material and method: twenty-one extracted single rooted teeth endodontically were treated, twenty teeth were obturated and divided into two groups according to method of resection. Group 1 root-end resected using cross cut carbide bur while group 2 root-end resected using laser with MGG6 sapphire tip of 600 μm diameter. Temperature on external root surface and duration of resection were recorded. The remaining tooth served as control. Samples were prepared for SEM and examined to evaluate dentinal cracks, cemental damage, roughness, filling material-root canal wall interface. Statistical Analysis: whenever required, x2 test/Fisher exact and Kruskal–Wallis test were used. Results: laser result in intradentin cracks in 70% of samples while bur cause intradentin crack in 30% of samples. There was no significant difference between group 1 and 2 regarding the percentage of complete and incomplete cracks. Resection with bur resulted in cemental damage in 70% of samples while resection with laser didn’t result in cemental damage in any of the samples .Evaluation of surface roughness revealed statistically significant difference (P ≤ 0.05). The difference in duration of resection was statistically significant while in recorded temperature was not significant. Conclusion: Er,Cr:YSGG laser showed higher percentage of intradentinal cracks, no cemental damage, larger gap area ,rougher surface and longer time for resection than bur .There is no elevation of temperature on external root surface.